Sleep‐wake cycle disturbances in elderly acute general medical inpatients: Longitudinal relationship to delirium and dementia. Issue 1 (21st January 2017) - FitzGerald, James M.; O'Regan, Niamh; Adamis, Dimitrios; Timmons, Suzanne; Dunne, Colum P.; Trzepacz, Paula T.; Meagher, David J.
Abstract: Introduction: Sleep disturbances in elderly medical inpatients are common, but their relationship to delirium and dementia has not been studied. Methods: Sleep and delirium status were assessed daily for a week in 145 consecutive newly admitted elderly acute general hospital patients using the Delirium Rating Scale‐Revised‐98 (DRS‐R98), Diagnostic and Statistical Manual 5, and Richards‐Campbell Sleep Quality Scale measures. The longitudinal relationship between DRS‐R98 and Richards‐Campbell Sleep Quality Scale sleep scores and delirium, also with dementia as a covariate, was evaluated using generalized estimating equation logistic regression. Results: The cohort was divided into delirium only, dementia only, comorbid delirium‐dementia, and no‐delirium/no‐dementia subgroups. Mean age of total group was 80 ± 6.3, 48% were female, and 31 (21%) had dementia, 29 had delirium at admission (20%), and 27 (18.5%) experienced incident delirium. Mild sleep disturbance (DRS‐R98 sleep item score ≥1) occurred for at least 1 day in all groups, whereas moderate sleep disturbance (score ≥2) occurred in significantly more of the prevalent delirium‐only (81%; n  = 17) cases than incident delirium‐only (46%; n  = 13) cases ( P  < .001). There were more cases with DRS‐R98 sleep item scores ≥2 ( P  < .001) in the delirium‐only group compared with the other subgroups. Severity of sleep‐wake cycle disturbance over time was significantly associated with Diagnostic and Statistical Manual 5 delirium status but not with age, sex, or dementia ( P  < .001). Conclusions: Observer‐rated more severe sleep‐wake cycle disturbances are highly associated with delirium irrespective of dementia status, consistent with being a core feature of delirium. Monitoring for altered sleep‐wake cycle patterns may be a simple way to improve delirium detection.